A mini-system for storage, retrieval and management of pacemaker data. - Salvador-Mazenq M; Candelon B; Graulle A; Puel P (Pacing & Clinical Electrophysiology, 1980)
Information processing is becoming a necessity for the management and the analysis of data at Cardiac Electrostimulation Centers, particularly since pacemaker implantation is becoming more frequent and the material more diversified. The mini system described allows retrieving of simple data and allows a real time acquisition of spike parameters by means of an electronic coupling unit with an impulse analyser. Its simplicity, availability and low cost are desirable qualities needed for the proper functioning of a Pacemaker Implantation Center.